Remote Household Observation for Noninfluenza Respiratory Viral Illness. (17th November 2020) - Emanuels, Anne; Heimonen, Jessica; O'Hanlon, Jessica; Kim, Ashley E; Wilcox, Naomi; McCulloch, Denise J; Brandstetter, Elisabeth; Wolf, Caitlin R; Logue, Jennifer K; Han, Peter D; Pfau, Brian; Newman, Kira L; et al.
Abstract: Background: Noninfluenza respiratory viruses are responsible for a substantial burden of disease in the United States. Household transmission is thought to contribute significantly to subsequent transmission through the broader community. In the context of the coronavirus disease 2019 (COVID-19) pandemic, contactless surveillance methods are of particular importance. Methods: From November 2019 to April 2020, 303 households in the Seattle area were remotely monitored in a prospective longitudinal study for symptoms of respiratory viral illness. Enrolled participants reported weekly symptoms and submitted respiratory samples by mail in the event of an acute respiratory illness (ARI). Specimens were tested for 14 viruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), using reverse-transcription polymerase chain reaction. Participants completed all study procedures at home without physical contact with research staff. Results: In total, 1171 unique participants in 303 households were monitored for ARI. Of participating households, 128 (42%) included a child aged <5 years and 202 (67%) included a child aged 5–12 years. Of the 678 swabs collected during the surveillance period, 237 (35%) tested positive for 1 or more noninfluenza respiratory viruses. Rhinovirus, common human coronaviruses, and respiratory syncytial virus were the most common. Four cases of SARS-CoV-2 were detected in 3 households. Conclusions: This study highlights the circulation of respiratory viruses within households during the winter months during the emergence of the SARS-CoV-2 pandemic. Contactless methods of recruitment, enrollment, and sample collection were utilized throughout this study and demonstrate the feasibility of home-based, remote monitoring for respiratory infections. Abstract : A household study using online recruitment and home collection of respiratory specimens was conducted in 303 households during the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Of 678 samples collected, 237 tested positive for 1 or more noninfluenza viruses, and 4 tested positive for SARS-CoV-2.